Antecedents Of The Intention To Use Chatgpt As A Tool For Shopping Information Search In Indonesia - Dwi Arbian Ilhami; Arif Hartono (Jurnal Ecogen, 2025)
Abstract:  The popularity of artificial intelligence (AI) technology has driven the creation of new strategies in online shopping, combining technological interaction and commercial transactions through the use of virtual assistants like ChatGPT. Although this technology is still in the exploration phase among consumers, several studies have attempted to uncover the factors influencing consumers' intention to use ChatGPT for product information search, such as performance expectancy, effort expectancy, facilitating conditions, hedonic motivation, habit, AI self-efficacy, perceived satisfaction, and social influence.  However, findings remain inconsistent. This study aims to address this gap by analyzing the determinants of consumers’ intention to use ChatGPT as a source of shopping information. A total of 269 active ChatGPT users participated, and the data were analyzed using SPSS and PLS-SEM via SmartPLS. The results show that performance expectancy, effort expectancy, facilitating conditions, hedonic motivation, habit, AI self-efficacy, and perceived satisfaction positively and significantly influence intention to use ChatGPT. Conversely, social influence shows no significant effect. This study contributes to marketing literature on AI usage in e-commerce and offers practical insights for marketing managers to design strategies that optimize ChatGPT to enhance consumer experience and promote AI adoption in the Indonesian market.